among the wheat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Herbicide Resistance and World Grains Edited by S Powles & D Shaner, CCpress, USA, 2001. 328 pp. ISBN/ISSN: 0849322197 US$ 99.95 Euro 113.20